Эмблемы с изображениями луны, солнца и драконов в костюме монгольской кочевой элиты XIII-XIV веков - Доде, З.В. (Степи Европы в эпоху средневековья, 2012)
The paper deals with a number of findings of medieval “Mongolian” clothes with a special decor, in particular oriental robes with the sleeves decorated with moon and sun images, oriental robes made of silk fabrics with the images of dragons, and oriental robes with the images of both dragons and heavenly bodies. Robes with these symbols were the property of the reigning house according to the medieval Chinese ceremonial. After the Jin and Southern Song dynasties fell, the Mongolian elite appropriated some of the Chinese imperial symbols. This paper is aimed at the elucidation of the meaning of these symbols on the costumes of nomads of the Mongolian empire.